Plasma Advanced Oxidative Protein Products are Associated with Anti-oxidative Stress Pathway Genes and Malaria in a Longitudinal Cohort. - Zhang, Guicheng; Skorokhod, O.; Khoo, S.; Aguilar, R.; Wiertsema, S.; Nhabomba, A.; Marrocco, T.; McNamara-Smith, M.; Manaca, M.; Barbosa, A.; Quintó, L.; Hayden, C.; et al. (BioMed Central Ltd, 2014)
BACKGROUND: Advanced oxidation protein products (AOPP) are newly identified efficient oxidative stress biomarkers. In a longitudinal birth cohort the effects were investigated of genetic polymorphisms in five oxidative pathway genes on AOPP levels. METHODS: This study is part of a three-arm randomized, double-blind, placebo-controlled trial. Three hundred and twelve children were included in the present study with AOPP levels measured at 2.5, 5.5, 10.5, 15 and 24 months of age. Twelve polymorphisms were genotyped in five oxidative stress pathway genes: glutathione reductase (GSR), glutamylcysteine synthetase (GCLC), glutathione S-transferase (GST) P1, haem oxygenase 1 (HMOX1) and superoxide dismutase 2 (SOD2) in 298 children. There were 284 children assessed for anaemia and clinical malaria infection at the age of 24 months. RESULTS: Two principal components (PCA1 and PCA2) were derived from the AOPP levels measured at the five time points. PCA1 was significantly associated with anaemia (p = 0.0002), and PCA2 with clinical malaria infection (p = 0.047). In the K-Means Cluster Analysis based on levels of AOPP, children were clustered into two groups: Group A (lower AOPP levels) and Group B (higher AOPP levels). The cluster membership was significantly associated with anaemia (p =0.003) as well as with the GSR RS3594 polymorphism (p = 0.037). Mixed linear regression analyses found that the single nucleotide polymorphisms GCLC RS10948751 and HMOX1 RS17885925 were significantly associated with AOPP levels (p = 0.030 and p = 0.027, respectively).CONCLUSION: Plasma AOPP levels were predictive for anaemia and oxidative stress markers for clinical malaria infection in two year old children. Several polymorphisms in GCLC, GSR and HMOX1 genes were associated with oxidative stress status of these children